Implementasi Kebijakan Program Keluarga Harapan di Kecamatan Rancasari Kota Bandung - Kartini, Entin; Susniwati, Susniwati (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
This study aims to examine and analyze the implementation of the Family Hope Program (Program Keluarga Harapan/PKH) policy in Rancasari District, Bandung City. In addition, it also analyzes the inhibiting factors affecting the implementation of the Family Hope Program policy and the efforts made to address challenges in the program's implementation in Rancasari District, Bandung City. The Family Hope Program (PKH) is a poverty alleviation initiative that supports access to healthcare services and improves the quality of life for poor and vulnerable families in terms of education and social services. Poverty issues arise when individuals are unable to meet their basic needs, thus requiring active government intervention to improve public welfare. The government provides PKH based on community data, which often proves to be inaccurate—some ineligible individuals are recorded in the central database as beneficiaries. Therefore, evaluation is needed to ensure the PKH policy is well-targeted so that it can truly help impoverished families enhance their quality of life. This study uses a descriptive method with a qualitative approach. The data analysis is qualitative and conducted using an inductive method. Data were collected through observation, interviews, and documentation. The interviews were conducted in a structured and in-depth manner, guided by an interview framework. The findings reveal that the implementation of the PKH policy in Rancasari District is generally in line with national guidelines, influenced by several factors such as resources, communication, disposition, and bureaucratic structure. However, several technical and social obstacles at the local level remain. Supporting factors include the existence of an electronic distribution system, commitment from PKH officers, and support from the local community. Meanwhile, inhibiting factors include inaccurate data on beneficiary families (KPM), high workload for facilitators, and low public understanding. Efforts to address these issues include data updating, facilitator training, increased outreach, utilization of information technology, and strengthened cross-sector collaboration.